Analysis of Women Empowerment through Sustainable Farming Education: Evidence from Karangcangkring Village, Indonesia - Dwiyana Anela Kurniasari; Teguh Soedarto (Agricultural Science, 2026)
Women play a strategic role in the agricultural sector and family food security, yet they still face limited access to agricultural education, technology, and decision-making. This situation contributes to low levels of empowerment of female farmers, particularly in rural areas. This study aims to analyze women's empowerment through sustainable agricultural education, using a case study in Karangcangkring Village, Gresik Regency, Indonesia. The study employed a case study approach with descriptive qualitative methods supported by simple quantitative data. Data collection was conducted through participant observation, semi-structured interviews, pre- and post-activity questionnaires, and focus group discussions. The analysis of women's empowerment was conducted with reference to the cognitive, economic, social, and institutional dimensions. The results indicate that sustainable agricultural education has a positive impact on increasing the empowerment of female farmers. The most significant improvements occurred in the cognitive and social dimensions, demonstrated by increased agricultural technical knowledge, self-confidence, and women's active participation in group activities and decision-making. The economic and institutional dimensions also showed positive, albeit gradual, developments, particularly in production management, post-harvest management, and women's involvement in agricultural group structures. Overall, sustainable agricultural education not only improves the technical capacity of women farmers but also strengthens their agency, social participation, and position within rural agricultural livelihood systems. This research confirms that the integration of gender-sensitive agricultural education is a crucial strategy for empowering women farmers and promoting inclusive and sustainable agricultural development at the village level.